Pyroptosis Induction and Detection. (20th July 2018) - den Hartigh, Andreas B.; Fink, Susan L.
Abstract: Pyroptosis is a form of programmed pro‐inflammatory cell death that plays a protective role in the host response to infection, but can also promote pathogenic inflammation. Pyroptosis is mediated by the cysteine protease, caspase‐1. Caspase‐1 cleaves gasdermin D, releasing the N‐terminal pore‐forming domain, which inserts into the plasma membrane and drives osmotic lysis. Caspase‐1 also proteolytically activates the inflammatory cytokines interleukin 1β (IL‐1β) and IL‐18. This unit describes methods for stimulating pyroptosis and assessing subsequent loss of plasma membrane integrity. We also describe an ELISA to quantify released IL‐1β. These methods can be applied to many different types of experiments. © 2018 by John Wiley & Sons, Inc.